Sraffa’s 1920s Critique and its Relevance for the Assessment of Mainstream Microeconomics - Brondino, Gabriel (2017)
The present essay re-examines the scope of Sraffa's critique of Marshall'ssupply curves that the former developed in his 1925 and 1926 articles showingthat neoclassical supply curves derived from non-proportional returns arenot robust both in the short and in the long run. After examining what ashort-run and a long-run equilibrium means both for the original Sraffa's articles and for Marshall?s pioneer contribution, the chapter discusses thecommon procedure in conventional economics to introduce the limitations tothe growth of the firm. The argument of the chapter will be based on the1920s articles as well as on the 'Lectures on Advanced Theory of Value' delivered in 19281931 by Sraffa at Cambridge University, now publiclyavailable online by the Wren library, Trinity College, Cambridge. For shortrunanalysis, it must be assumed that the number of firms is fixed. Thisassumption entails serious problems with regards to the notions of competitionand competitive behaviour. For long-run analysis, the sources of increasingcosts are problems of management and control. However, this idea isuntenable both on logical and empirical grounds. We argue that contemporarymainstream microeconomic treatment of costs and supply in the contextof perfect competition still presents several problems. These problems, rather than being superficial, lie at the root of the supply and demand approach ofvalue and distribution.